The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1472-8206.1999.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of MET‐88 on left ventricular dysfunction and hypertrophy with volume overload in rats

Abstract: We examined the effects of MET-88 on haemodynamics and cardiac hypertrophy in rats with an aortocaval shunt (A-V shunt). On the day of surgery, an A-V shunt was produced by using an 18-gauge needle in Wistar rats as described by Garcia and Diebold. MET-88 and captopril were orally administered to rats 1 week after surgery, and the administration was continued for 3 weeks. Four weeks after the surgery, A-V shunt-operated rats had biventricular hypertrophy and higher right atrial pressure (RAP) and left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…The infarcted area was reduced from 30 to 19% [58]. MET-88 attenuated also left ventricular dysfunction in rats with an aorto-caval shunt [88].…”
Section: Gamma-butyrobetaine Hydroxylase Inhibitorsmentioning
confidence: 99%
“…The infarcted area was reduced from 30 to 19% [58]. MET-88 attenuated also left ventricular dysfunction in rats with an aorto-caval shunt [88].…”
Section: Gamma-butyrobetaine Hydroxylase Inhibitorsmentioning
confidence: 99%
“…Mildronate induces significant attenuation of the development of left ventricular (LV) hypertrophy and of increased LVEDP. These results suggest that mildronate improved LV hypertrophy and LV dysfunction in rats with heart failure induced by myocardial ischemia (Nakano et al, 1999). In a similar study performed by Hayashi et al, the effects of mildronate were examined in rats with congestive heart failure following myocardial infarction (Hayashi et al, 2000b).…”
Section: Heart Failurementioning
confidence: 67%
“…In contrast, MET-88 did not affect coronary flow before ischemia. We demonstrated that MET-88 had no effect on blood pressure and heart rate in rats and dogs [10,19]. Also, MET-88 (bolus injection into the coronary artery) showed no effect on coronary blood flow in anesthetized dogs [unpubl.…”
Section: Discussionmentioning
confidence: 99%